DOMESTIC VIOLENCE IN JAMMU AND KASHMIR: - A STUDY. - PRIKSHA RAINA (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
ABSTRACT Women are becoming the victims due to domestic violence, social practices, armed conflict, and militancy in the state. They are not only suffering from penetrating humiliation and harassment but also suffering from shocking experiences with continued depression that left them mentally ill. The conflicting situation in Jammu and Kashmir has snatched the women’s right and hit their hardship. No one knew how many women became widow and also having the responsibility of upbringing their children. The researcher used the secondary sources of data and came to the conclusion that women in many regions of Jammu and Kashmir are still facing the issues and challenges related to education, health, domestic violence, politics, declining sex ratio, state violence, dowry harassment, eve teasing, unequal wage, child labour and female feticide and infanticide etc. To overcome these issues central government, state government and NGOs should work together for the empowerment of women in Jammu and Kashmir.